(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Educational upbringing is of particular importance in the development of the national economy. Education is one of the main elements in the social economic development of the country. President of the Republic of Uzbekistan Shavkat Mirziyoyev emphasized the implementation of education and science, the state’s policy on youth, the implementation of urgent tasks in the field of introducing new, modern methods of education, including information and communication technologies, and the development of education and science as a component in the development of the social sphere.